Senam Sehat Upaya Merdeka Dari Penyakit Bersama Masyarakat Kuta Bayu Kab. Deli Serdang - Ramadhani, Mastari; Mlinda, Leni; Herdyana, Thessa; Hariati, Emy; Putri, Nizmi; Safitri, Layil; Ramadianti, Astria Ayu; Harahap, Syarifah Ainun; Hidayat, Wahyu; Ritonga, Zon Saroha; Lubis, Rizka Hidayah Husein; Fahri, Romi; Yanti, Sisilia Florina (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2023)
Community service activities for lecturers are an effort to carry out one of the tridharma tasks of higher education. Community service carried out in the form of gymnastics activities with the theme Efforts to Be Free from Disease Together with the Kuta Bayu Community in Gunung Meria District, Deli Serdang Regency. This activity aims to carry out the tridharma activities of higher education lecturers in order to contribute knowledge and outreach to society. This service carried out by several lecturers at Nahdlatul Ulama University, North Sumatra (UNUSU) invites the people of Kuta Bayu to start doing regular exercise activities in order to have a healthy physique and avoid all forms of disease. The expected output target of this activity is: to provide an understanding that Doing gymnastics provides many benefits for the body's health, one of which is improving the body's metabolic system and increasing and strengthening the immune system in the body to avoid various diseases.